Control of the Alphitobius diaperinus (Panzer) (Coleoptera: Tenebrionidae) with entomopathogenic fungi - Rezende,SRF (2009)
The beetle Alphitobius diaperinus (Panzer), considered a worldwide pest in the poultry industry, is difficult to control and it is a vector for pathogens. The objective of this study was to evaluate the biological control of the lesser mealworm, by strains of fungi Beauveria bassiana, Cladosporium sp. and Trichoderma sp. Larvae and adults of the A. diaperinus were inoculated with suspensions of conidia in the concentration of 10(7) conídia.mL-1. The B. bassiana isolate caused higher insect mortality as compared to Cladosporium sp. and Trichoderma sp. isolates, with the larvae being more susceptible than adults. The entomopathogenicity of B. bassiana was further evaluated with 200 larvae and 200 adults of A. diaperinus inoculated with suspensions 10(6), 10(7), and 10(8) conidia.mL-1, and observed for ten days. Larvae mortality started at the fourth day at the lowest concentration, and the adult mortality was only observed on the sixth day at the concentration of 10(8) conidia.mL-1.